2011
DOI: 10.21236/ada538618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Relationships Between Reported Resilience and Soldier Outcomes. Report #1: Negative Outcomes (Suicide, Drug Use, & Violent Crimes)

Abstract: This document is the first of a series of reports evaluating the impact of the Army's Comprehensive Soldier Fitness (CSF) Program by examining relationships between reported resilience and various health and behavioral outcomes (both positive and negative) among Soldiers. The first set of deidentified Global Assessment Tool data made available for analysis included responses from Soldiers who completed suicide in 2010, Soldiers who tested positive for illicit drug use, and Soldiers who were charged with engagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Thus, every year, and for every component of the GAT, some percentage-whose value depends only on where the reporting threshold is set-of subjects will be told that they need to improve on that component, regardless of any prior improvements in the absolute level of that component that those subjects, or the Army as a whole, might have made. Confirmation of this approach can be found in Lester, Harms, Bulling, et al (2011a), in which an apparently positive Likert-scale score of 3.84 out of 5 is shown with a red bar ("facing some significant challenges") because it is slightly lower than the average score for the comparison group (see Figure 2). Thus, the GAT will always "reveal" that large numbers of soldiers are facing "significant challenges"-and, hence, are deemed to be in need of further resilience training-by a process that appears to consist of circular reasoning.…”
Section: Issues With the Design And Deployment Of The Gatmentioning
confidence: 60%
See 4 more Smart Citations
“…Thus, every year, and for every component of the GAT, some percentage-whose value depends only on where the reporting threshold is set-of subjects will be told that they need to improve on that component, regardless of any prior improvements in the absolute level of that component that those subjects, or the Army as a whole, might have made. Confirmation of this approach can be found in Lester, Harms, Bulling, et al (2011a), in which an apparently positive Likert-scale score of 3.84 out of 5 is shown with a red bar ("facing some significant challenges") because it is slightly lower than the average score for the comparison group (see Figure 2). Thus, the GAT will always "reveal" that large numbers of soldiers are facing "significant challenges"-and, hence, are deemed to be in need of further resilience training-by a process that appears to consist of circular reasoning.…”
Section: Issues With the Design And Deployment Of The Gatmentioning
confidence: 60%
“…The first of these (Lester, Harms, Bulling, et al, 2011a) demonstrated that soldiers who committed suicide,…”
Section: Preliminary Results Of Csfmentioning
confidence: 99%
See 3 more Smart Citations